Analysis of the effect of LMO2 on indicating CD8+ T-lymphocyte infiltration in pan-cancers - Yu, Yanhong; Yuan, Mei; Zhang, Zhao; Wang, Dan; Sun, Wei (Biochemistry and biophysics reports, 2025)
LMO2 is a critical factor in hematopoiesis but widely expressed in kinds of epithelia and solid tumors as well, and it has been demonstrated that increased LMO2 level in some tumor cells exhibits an effect on promoting CD8+ T-lymphocyte infiltration in tumor microenvironment. Herein we expanded the investigation of such effect in pan-cancer spectrum, and the transcriptome data analysis revealed extensively positive associations between LMO2 and CD8+ T-lymphocyte infiltration in pan-cancers. Meanwhile, tissue staining revealed variable expression level and consistently cytosolic localization of LMO2 in different tissues and their tumor counterparts, and further indicated that high LMO2 expression in malignant cells was strongly associated with positive CD8+ T-lymphocyte infiltration selectively in digestive tract, breast and kidney tumors. Taken together, this study depicted an overall view of LMO2 functional linkage with tumor immunology in pan-cancers and provided novel insight of LMO2 significance in the field of tumor immune therapy. [Display omitted] •LMO2 is commonly associated with T-lymphocyte gene module in tumor datasets.•LMO2 expression level in tumor cells varies depending on tissue type.•LMO2 is an effective indicator of CD8+ T-cell infiltration in certain tumors.